Conceptualization of the city and its territory. Geometric trend of the urban imaginary - Goytia Goyenechea, Lola; Martínez-Roldán, Nieves (Estoa. Journal of the Faculty of Architecture and Urbanism, 2020)
Man, in his environment, through perception and his intellectual resources, has always processed the stimuli received. Based on it, he has conceptualized: an idea of ​​the city in which he inhabits, built by him; a perception of the territory in which he lives, which he has transformed over time; and a notion of the world in which he is immersed, which he has managed to interpret. This conceptualization progressively generated from the origins of man has left us images of his representation that allow us to rigorously approach his knowledge, through the analysis of its contents and the contexts in which they have been generated. From this it follows that what man is able to conceptualize from the visual always means a certain spatial understanding, being in the urban frequently of geometric tendency, and this is fundamentally the abstract reference of a concrete reality that has its corresponding reflection in the representation.